2018
DOI: 10.1021/acsenergylett.7b01330
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Localized Energy States in Silicon-Doped InGaN Nanowires Using 4D Electron Microscopy

Abstract: Introducing dopants into InGaN NWs is known to significantly improve their device performances through a variety of mechanisms. However, to further optimize device operation under the influence of large specific surfaces, a thorough knowledge of ultrafast dynamical processes at the surface and interface of these NWs is imperative. Here, we describe the development of four-dimensional scanning ultrafast electron microscopy (4D S-UEM) as an extremely surface-sensitive method to directly visualize in space and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Meanwhile, a higher concentration of trapping states can also quicken the subsequent electron–hole recombination after the initial photoexcited charge carrier separation, revealing the reason why the decay rates for doped sample with Si at 1200 °C is larger than both doped sample at 1150 °C and undoped sample in the longer time regime (Figure e). Moreover, these results were corroborated by numerical simulations and conductivity studies with/without light illumination and deepened the understanding of how Si doping affects the charge carrier dynamics and performance of InGaN/GaN nanowire-based optoelectronic devices …”
Section: Emerging Applicationsmentioning
confidence: 59%
See 1 more Smart Citation
“…Meanwhile, a higher concentration of trapping states can also quicken the subsequent electron–hole recombination after the initial photoexcited charge carrier separation, revealing the reason why the decay rates for doped sample with Si at 1200 °C is larger than both doped sample at 1150 °C and undoped sample in the longer time regime (Figure e). Moreover, these results were corroborated by numerical simulations and conductivity studies with/without light illumination and deepened the understanding of how Si doping affects the charge carrier dynamics and performance of InGaN/GaN nanowire-based optoelectronic devices …”
Section: Emerging Applicationsmentioning
confidence: 59%
“…Therefore, the enhanced PCE can be reasonably attributed to the lower density of the surface states after treatment, which suppresses nonradiative recombination channels . Moreover, S-UEM is also capable of exploring how Si doping affects the photophysics of InGaN/GaN nanowires (Figure e,f) . Interestingly, it was demonstrated that, with Si doping, the specimen exhibits a faster charge carrier recombination in a longer time regime and a slower charge separation at a shorter time scale, compared to that with the undoped specimen.…”
Section: Emerging Applicationsmentioning
confidence: 95%
“…[12] Very recently, NPC was reported for Si-doped InGaN nanowires, which was attributed to carrier-carrier scattering owing to high carrier concentration. [42] Since the carrier generation and recombination are energetic processes, [43] one expects the results could have dependence on the illumination conditions and measurement temperature.…”
mentioning
confidence: 99%
“…Four-dimensional scanning ultrafast electron microscopy (4D S-UEM) is the sole technique capable of the surfaceselective visualization of the light-triggered carrier dynamics at the angstrom-nanometer scale. [48][49][50][51][52][53][54][55] 4D S-UEM uses an electron probing system to scan the top surface of the photoactive materials after being pumped with a photon pulse. As a result, secondary electrons are ejected from the top few nanometers (< 5 nm) and can be detected in real space and time.…”
Section: Toc Graphicmentioning
confidence: 99%
“…However, the large penetration depth of light, especially in Si (∌1330 nm at a light wavelength of 515 nm), hinders the selectivity of discerning the native oxide layer that has at most a 2 nm thickness without the interference of the bulk properties when using a photon pump in the photon probe configuration. Four-dimensional scanning ultrafast electron microscopy (4D S-UEM) is the sole technique capable of the surface-selective visualization of the light-triggered carrier dynamics at the angstrom–nanometer scale. − 4D S-UEM uses an electron probing system to scan the top surface of the photoactive materials after being pumped with a photon pulse. As a result, secondary electrons are ejected from the top few nanometers (<5 nm) and can be detected in real space and time.…”
mentioning
confidence: 99%